2021
DOI: 10.1155/2021/6677437
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Quantification of Luteolin-Metal Complexes in Aqueous Extract of Lonicerae Japonicae Flos and Huangshan Wild Chrysanthemum

Abstract: Luteolin is a flavonoid compound widely found in vegetables, fruits, and medicinal plants. In this study, the reaction conditions for luteolin and five metal ions (Ca2+, Mg2+, Zn2+, Fe3+, and Cu2+) to form complexes in hot water were optimized, which was at a molar ratio of 1 : 1 for luteolin and metal ions at 90°C in a volume of 20 mL for 2 h, and the ability of luteolin to form complexes with Cu2+ was the strongest. The DPPH scavenging test showed that luteolin exerted a dose-dependent effect on the clearanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Luteolin, as a flavonoid, can complex with metal ions to assemble into nanostructured materials. 21 The transmission electron microscope (TEM) image of CeLutNCs revealed their irregular spherical shape with an average diameter of 60 nm, and elemental mapping demonstrated the copresence and distribution of C, O, and Ce elements (Figure 1b). The powder X-ray diffraction (XRD) pattern in Figure 1c showed that the CeLutNCs were amorphous without the detection of crystallized Ce-containing phases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Luteolin, as a flavonoid, can complex with metal ions to assemble into nanostructured materials. 21 The transmission electron microscope (TEM) image of CeLutNCs revealed their irregular spherical shape with an average diameter of 60 nm, and elemental mapping demonstrated the copresence and distribution of C, O, and Ce elements (Figure 1b). The powder X-ray diffraction (XRD) pattern in Figure 1c showed that the CeLutNCs were amorphous without the detection of crystallized Ce-containing phases.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, CeLutNCs were obtained by mixing Ce­(NO 3 ) 3 with a luteolin ethanol solution in the presence of polyethylene glycol (PEG) 8000 at room temperature (Figure a). Luteolin, as a flavonoid, can complex with metal ions to assemble into nanostructured materials . The transmission electron microscope (TEM) image of CeLutNCs revealed their irregular spherical shape with an average diameter of 60 nm, and elemental mapping demonstrated the copresence and distribution of C, O, and Ce elements (Figure b).…”
Section: Results and Discussionmentioning
confidence: 99%
“…For instance, as flavonoids have chelating properties, their antioxidant activity is determined by the concentration of copper (Cu), cadmium (Cd), and iron (Fe) in cells. It has been proven that under low Fe 3+ concentrations, luteolin acts as an antioxidant agent, whereas increased concentration stimulates its pro-oxidant activity [25,26]. The understanding of the mechanisms by which luteolin can behave in certain ways is incomplete and thus requires further examination.…”
Section: Introductionmentioning
confidence: 99%